(3cTa GdQjH aj GdYed HGdLjHs - (3eMeO Hf CMeO Hf YHO GdQMje GdeRj GdeGdcj , TeS GdOjf,J (B750 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLg (B: (3Cfg djS ai GdBdGJ Gdadcjg eG jYed Hg LejY GdCYeGd ai cd YQT HChVM WQjb ZjQ GdLjH s
(3BNQgG (B:s
(3hjbSe Pdc Ydi LjH GdGQJaGY ajNQL Xd GdeHShW hYedg s
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B327 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B275s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B85 s
Keywords: (3Gdadcs